Conflicts within Mekong river region : an analysis on the capacity of Mekong river commission. - Xu, Shasha. (2013)
The Mekong River Commission (MRC) was built in 1995 for the purpose of sustainable development of Mekong River. Based on the Neoliberal Institutionalism, the cooperation and instruments could be conducive to solving hydro-political